First Evidence of Potential Microplastic Ingestion of Yellow Striped Goat Fish Upeneus vitattus (Forsskal, 1775) Caught in Malita, Davao Occidental, Philippines - Bersaldo, Michael Jeriel Inocentes; Lacuna, Maria Lourdes Dorothy G.; Orbita, Maria Luisa S.; Tampus, Annielyn D.; Avenido, Pedro M.; Macusi, Edison D. (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Microplastic (MP) study in the Philippines is gaining attention because of the recent trends in macro-microplastic study worldwide and there is already a call for research to help the degrading marine environment in the country. No study in Malita, Davao Occidental was conducted to document microplastic contamination. To address this gap, 30 goat fishes collected in 6 sampling stations were dissected and microplastic were extracted, counted, and characterized. Results revealed that 96.67% of samples were contaminated with microplastic. In terms of microplastic type, fiber was most dominant than fragments, in microplastic hue, color black was the most common and microplastic with size ranging from 50 to 500µm were usually observed. Comparable amount of microplastic was obtained in fish guts across stations (P>0.05) which means that fish ingestion of microplastic were evident in the area. Based on Correlation, the length (r2=0.13), wet weight (r2=0.17) and gut wet weight (r2=0.29) of the fish does not tell the amount of microplastic ingested by each yellow stripped goat fish since there is a weak relationship between the two parameters. The result suggests, Malita’s seawater is already polluted with microplastic and demersal fishes that practice high site fidelity were very susceptible to microplastic ingestion. A stronger solid waste management policy must be implemented and activities such coastal clean ups and information drives must be initiated by all stakeholders. Further, microplastic investigation in seawater and sediments must be conducted to have a more detailed study of the whole extent of microplastic contamination in Malita, Davao Occidental.